Curved approach in high jump induces greater jumping height without greater joint kinetic exertions than straight approach - Sado, N.; Yoshioka, S.; Fukashiro, S. (Medicine & Science in Sports & Exercise, 2022)
Purpose The most height-specific jumping mode, the athletic high jump, is characterized as a running single-leg jump (RSLJ) from a curved approach. The main advantage of a curved approach is believed to be facilitation of bar clearance. However, the effect of a curved approach on center-of-mass (CoM) height generation has not been clarified. Here, we show that the curved RSLJ (C-RSLJ) is more suitable than the straight RSLJ (S-RSLJ) for CoM height generation.